PENDAMPINGAN DESAIN KEMASAN PADA KOMUNITAS KULINER KOTA PANGKALPINANG DALAM MENINGKATKAN DAYA SAING PRODUK - Occa Roanisca; Devi Valeriani; Herry Marta Saputra; Nurhadini Nurhadini; Eva Helda; Ristika Oktavia Asriza (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2023)
Micro, Small and Medium Enterprises (MSMEs) play a very strategic role in community-based economic development in Indonesia. The existence of MSMEs has been proven to be able to survive when facing a crisis. This is because MSMEs are only on a small scale, so the business capital requirements are small, and they are able to adapt to market needs. Aspects that are very important to support the existence of MSMEs are business legality, packaging design and digital-based marketing. The Culinary Community of Pangkalpinang City has superior products. The products have been marketed to the public and are often offered at District, Regency and Provincial level exhibitions. However, these products do not yet have an attractive and safe packaging design. Based on the results of an audience with the Culinary Community administrators, to overcome this problem assistance is needed for MSME actors to design packaging for the Culinary Community. This activity will involve the management of the Culinary Community by facilitating several products to make packaging designs attractive and safe. To realize this there are several problems that partners (MSMEs) have, namely: lack of knowledge about designing stickers and product packaging in an attractive and safe manner. Solutions that can be offered to help partners by socializing and assisting safe and attractive sticker and packaging designs. To reach a wider market share, socialization and assistance is carried out in designing stickers and packaging. This community service activity went well. The results of the socialization activities found that the target partners understood the importance of packaging designs that were attractive, informative and could be used as promotions. Partners understand packaging can increase product sales. At the end of the mentoring activity, the service team facilitated and handed over standing pounch packages made of aluminum foil to three target partners representing the culinary community of Pangkalpinang City. The hope of the Pangkalpinang City Tourism Office is that this community service activity can continue to increase the existence and development of culinary delights in Pangkalpinang City.